Collaborative group work in mathematics in the UK and Japan: use of group thinking measure tests. Issue 2 (17th February 2021) - Fujita, Taro; Doney, Jonathan; Flanagan, Ruth; Wegerif, Rupert
ABSTRACT: This paper reports on a study of collaborative group work in mathematics. Although collaborative group work is known as one of the important approaches in education, it is still uncertain how group thinking can be measured in various learning contexts. We used the Group Thinking Measure (GTM) test developed by [Wegerif, R., T. Fujita, J. Doney, J. Perez Linares, A. Richards, and C. van Rhyn. 2017. "Developing and Trialing a Measure of Group Thinking." Learning and Instruction 48: 40–50.] alongside mathematics tests to measure group thinking and group mathematical thinking. Our participants from Japan (134 pupils, 10–12 year old) and the UK (30 pupils, 11–12 year old) schools undertook the GTM individually and then in a group of three (triad), following which, the same group also solved sets of mathematics problems. From the quantitative results we found that examining whether a group is a Value Added Group or not in their GTM scores is a useful way to identify more mathematically effective groups. From a qualitative analysis of video data of pupils' group work, we also found that successful problem solving might be due to the use of certain strategies. In conclusion, we consider that GTM can be used to indicate which groups are effective in subject areas such as mathematics.